2013
DOI: 10.1039/c3sc22240c
|View full text |Cite
|
Sign up to set email alerts
|

CO2 as a C1-building block for the catalytic methylation of amines

Abstract: A novel catalytic reaction has been designed to utilize, for the first time, CO 2 as a C 1 feedstock in the synthesis of N-methylamines. Simple zinc catalysts, based on commercially available zinc salts and ligands, prove highly efficient in promoting both a 6 electron reduction of carbon dioxide and the formation of a C-N bond, using hydrosilanes and amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
178
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(192 citation statements)
references
References 34 publications
2
178
0
12
Order By: Relevance
“…3, equation c) 32 . In the same year, Cantat et al 33 reported zinc catalysts able to perform the methylation of amines with CO 2 and hydrosilanes at low pressure. Furthermore, the selective reduction of ureas was possible under similar reaction conditions.…”
Section: Box 1 | Coordination Modes Of Co 2 With Transition Metalsmentioning
confidence: 99%
“…3, equation c) 32 . In the same year, Cantat et al 33 reported zinc catalysts able to perform the methylation of amines with CO 2 and hydrosilanes at low pressure. Furthermore, the selective reduction of ureas was possible under similar reaction conditions.…”
Section: Box 1 | Coordination Modes Of Co 2 With Transition Metalsmentioning
confidence: 99%
“…Carbon dioxide is a waste product from all combustion processes and represents a potential and alternative carbon feed stock 1,2 for the preparation of a variety of useful chemicals including MeOH, 3,4 urea, 5 lactones, 6 various heterocycles, [7][8][9][10][11] biodegradable polymers, [12][13][14][15][16] and carboxylated structures [17][18][19][20][21] among others. [22][23][24] In particular, direct CO 2 utilisation for the preparation of polycarbonates, poly(ether)carbonates and polyurethanes is a viable technology to access novel tailor-made CO 2 -based materials. 25 The development of cost-and energy-efficient synthetic methodologies to exploit CO 2 as a C 1 synthon could eventually loosen the grip on our fossil fuel dependence, contributing to a reduction of the overall CO 2 emissions and offering tangible alternatives to physical sequestration methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Zn(II)-NHC complexes represent a remarkable example. They have shown to be particularly active in reactions involving the fixation of CO 2 , such as the methylation of amines [3], or the synthesis of cyclic carbonates from epoxides [4]. In addition, they are employed in the synthesis of polyurethanes [5] and in the polymerization of D,L-lactide [6].…”
Section: Introductionmentioning
confidence: 99%